Presence and Future of the Professional Rehabilitation System. Propositions of Changes Based on the Analysis of Existing Instruments of Support - Skiba, Wojciech (Warsaw Forum of Economic Sociology, 2020)
The subject of the article is the analysis of the most important reasons for low effectiveness of key instruments of social policy in the area of vocational rehabilitation of people with disabilities. On its basis, proposals for changes in social policy were formulated, which could contribute to improving the effects of the implemented policy.